Analysis and Review on By-Products of Banana: Exploring the diversity and uses of banana by-products (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The banana is a consumable natural product, organically aberry, created by a few sorts of expansive herbaceous blossoming plants inthegenus Musa.[3] In a few nations, bananas utilized for cooking may be calledplantains. The natural product is variable in size, shading and immovability,however is generally prolonged and bended, with delicate tissue rich in starchsecured with a skin which may be green, yellow, red, purple, or cocoa whenready. The organic products develop in groups swinging from the highest pointof the plant. All cutting edge edibleparthenocarpic (seedless) bananasoriginate from two wild species – Musa acuminata and Musa balbisiana. Thelogical names of most developed bananas are Musa acuminata, Musa balbisiana,and Musa × paradisiaca for the mixture Musa acuminata × M. balbisiana,contingent upon their genomic constitution. The old logical name Musa sapientumis no more utilized.